Analisis Perubahan Penggunaan Lahan Di Kecamatan Gunungpati Kota Semarang Tahun 2004 Dan Tahun 2011 - Nugroho, Tegar; , Dr. Kuswaji Dwi Priyono, M.Si; , Ir. Taryono, M.Si (2015)
This study aims to determine the distribution of land use change in the District Gunungpati that occurred between 2004 and 2011 and Knowing the factors affecting changes in land use in the District Gunungpati 2004 and 2011. The method used in this research is secondary data analysis method. Secondary data such as statistical data of land use Subdistrict Gunungpati 2004 and 2011, population growth, population density, increase social and economic facilities, as well as the District Gunungpati Map land use in 2004 and 2011. In this study, changes in land use in question is a change in land use agriculture to non-agriculture. The results of this research are village that experienced a high rate of change is the Village have now covering 129 ha (11.82%) and Sub Kandri covering 109 ha (9.99%) of the total change in the District Gunungpati Covering an area of ​​1,090 ha. From the results of the classification of the distribution of land use change and overlay maps distribution pattern changes in land use in the area of ​​research likely to lead to the East in the Village Kandri and to the west of the village have now. Factors that influence the changes in land use in the study area is a factor of population growth and population density factor. Keywords: Land Use, Population Growth, Population Density